Surgical treatment can provide the opportunity for in-vitro fertilization (IVF) in a shorter period of time for patients with early-stage endometrial cancer - Qianhua Xu; Hedong Lu; Xiaolei Wang; Min Li; Weiwei Zou (Discover Oncology)
Abstract Background Whether localized surgical treatment has advantages over traditional hormone therapy for young women who desire to preserve their fertility and have Stage 1a and Grade 1 endometrial cancer. Case presentation We present a case study of a patient who was diagnosed with endometrial cancer (Grade 1a, Stage 1) and was experiencing infertility. The patient underwent conservative surgical treatment and was able to successfully conceive through in vitro fertilization (IVF). She delivered a healthy male child. The treatment involved hysteroscopic excision of the lesion followed by three cycles of transplantation. In the third cycle, endometrial preparation was done through HMG injection. On the 24th day of transplantation, an ultrasound was performed which indicated an intrauterine pregnancy. The patient received routine obstetric care and delivered a male baby via cesarean section at 38 weeks of gestation. The baby had an Apgar score of 10. (After delivery, follow up for a check-up). Conclusions Conservative surgical treatment of Stage 1a and Grade 1 endometrial cancer can reduce the treatment duration compared to conventional hormonal therapy. This indicates that conservative surgical treatment of early-stage endometrial cancer followed by in-vitro fertilization (IVF) is a feasible alternative for young women who desire to preserve their fertility.